2019
DOI: 10.1155/2019/4989013
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of the Forces Exerted during Different Occlusion Conditions following Bilateral Sagittal Split Osteotomy Treatment for Mandibular Deficiency

Abstract: The bilateral sagittal split osteotomy (BSSO) technique is commonly used to correct mandibular deficiency. If the patient is exposed to excessive external forces after the procedure, occlusal changes or nonunion may occur. However, previous studies only focused on single external forces on the mandible and did not conduct relevant research on the forces exerted by different occlusion conditions. The main purpose of this study was to use finite element analysis methods to determine the biomechanics of four comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…However, an oblique force of 105 N can induce tension in the cervical zone (SRIREKHA; BASHETTY, 2013;GUIMARÃES et al, 2014;CHANG et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an oblique force of 105 N can induce tension in the cervical zone (SRIREKHA; BASHETTY, 2013;GUIMARÃES et al, 2014;CHANG et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…INTRODUCTIONNon-carious cervical lesions, especially the abfraction type lesions, are loss of dental structure close to the cemento-enamel junction, without bacterial involvement, presenting a wedge shape. The etiology of these structural losses is often multifactorial and the evidence supports that inappropriate occlusal forces are related to the emergence of the abfraction (SRIREKHA;BASHETTY, 2013;CHANG et al, 2019;HARALUR et al, 2019). flexion, the occlusal forces are dissipated from the axial axis towards the cervical zones and the chemical bonds of the enamel hydroxyapatites can be damaged, initiating the loss of structure in this region (SADAF; AHMAD, 2014; MARINESCU et al,…”
mentioning
confidence: 99%
“…These FE results agreed with those of previous studies on the BSSO surgery. 11,17,35 Takahashi et al 11 found that the highest concentration of the mechanical stress occurred at the screw site and upper border of the miniplate near the fracture site. Erkmen et al 17 investigated the stress distributions for four different fixation methods, and also found that the maximum stress accumulated at the center of the miniplate near the fracture site.…”
Section: Discussionmentioning
confidence: 99%
“…Erkmen et al 17 investigated the stress distributions for four different fixation methods, and also found that the maximum stress accumulated at the center of the miniplate near the fracture site. In addition, Chang et al 35 evaluated the stress on the miniplate and screws, under four occlusal conditions, and found the highest stress at the screw close to the fracture gap.…”
Section: Discussionmentioning
confidence: 99%
“…, an oblique force of 105 N can induce tension in the cervical zone (SRIREKHA;BASHETTY, 2013; GUIMARÃES et al, 2014;CHANG et al, 2019).In the cervical zone of the dental elements, there is a transition in the orientation of the hydroxyapatite prisms that comprise them. When approaching the cementitious junction, there is a tendency to flatten and reduce the thickness of the enamel, in addition to having a lower mineral density.…”
mentioning
confidence: 99%